Antibody-drug conjugates for multiple myeloma. (3rd July 2021) - McMillan, Annabel; Warcel, Dana; Popat, Rakesh
ABSTRACT: Introduction: Antibody-drug conjugates (ADC) are a new class of treatment for multiple myeloma (MM) patients, delivering a potent cytotoxic agent directly to the myeloma cell. The target is defined by the specificity of the monoclonal antibody which is linked to the cytotoxic agent. This mechanism of action minimizes bystander cell injury and allows a favorable therapeutic window. Areas covered: This review describes the rationale, pre- and clinical data for ADCs that have been and are currently in development for MM. As the treatment landscape for MM rapidly evolves, the treatment paradigm and a description of novel agents in development including immunotherapies are provided to understand how ADCs may fit in the pathway. Expert opinion: ADCs have a significant potential for the treatment for MM. As they are 'off the shelf' treatments, they can be used across nearly all MM treatment centers and to a wide range of patients. Some ADCs have specific adverse events that may require specialist input to optimally manage. The most clinically advanced ADC is belantamab mafodotin which has demonstrated clinically meaningful responses in patients with heavily pre-treated MM. Additionally, it is being combined with standard of care agents and at earlier lines of treatment.